DAKWAH DAN DEMOKRASI :ANALISIS TENTANG KONTRIBUSI DAKWAH DALAM PENEGAKAN DEMOKRASI - Choiriyah Choiriyah; Zhila Jannati (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2020)
One of the important points in the process of da'wah is the content of the message. Namely the teachings contained in the Qur'an, al-Hadith, Ijma 'Ulamak and Qiyas. Meanwhile, the purpose of preaching itself is to make Islamic teachings manifest in every aspect of people's lives, the economic aspects are colored by Islamic teachings, as well as aspects of law, as well as politics and so on. Democracy as a form of government that is carried out by placing the people as holders of sovereignty, requires people who understand this role. There are three roles of the ummah in this case, namely electing a leader or head of government, exercising control over government policies and determining the goals the government must achieve. Therefore, Islamic communication or da'wah activities in this case need to contribute in an effort to educate the people so that they can play these roles. The contribution of da'wah in this case is to provide information about the criteria for a leader who is eligible to be elected, to provide information about policies such as what the government needs to do and the goals or directions that need to be taken.